Regional brain activity during jaw clenching with natural teeth and with occlusal splints: a preliminary functional MRI study. Issue 3 (3rd May 2016) - Ariji, Yoshiko; Koyama, Shuji; Sakuma, Shigemitsu; Nakayama, Miwa; Ariji, Eiichiro
Abstract: Objective: The purpose of this study was to investigate regional brain activity during jaw clenching with natural teeth and with two types of occlusal splints using functional magnetic resonance imaging (fMRI). Methods: Sixteen healthy volunteers were enrolled in this study. Blood oxygenation level-dependent (BOLD) fMRI signals were compared under three conditions: during clenching with natural teeth, with a soft splint, and with a hard splint. For each condition, 30-second jaw clenching followed a 60-second rest, and was repeated three times, with intervening 30-second rests. SPM 8 was used for the fMRI analysis. Results: Blood oxygenation level-dependent signals during clenching with natural teeth increased in BA44, 45, and the cerebellum. Blood oxygenation level-dependent signals increased in those areas and in BA17, 18 during clenching with a soft splint. Use of the hard splint increased the BOLD signals in BA6 and BA20, 37 in addition to the areas previously mentioned. Blood oxygenation level-dependent signals in the left BA6, the left BA20, 37, and the right BA44, 45 were significantly higher during clenching with a hard splint than with natural teeth. These regions are associated with motor coordination, memory, and cognition, respectively. Conclusion: Jaw clenching with a hard splint caused activity in the widest brain regions, including the associated area with motor coordination.